2015
DOI: 10.1038/jcbfm.2014.245
|View full text |Cite
|
Sign up to set email alerts
|

Rewarming from Therapeutic Hypothermia Induces Cortical Neuron Apoptosis in a Swine Model of Neonatal Hypoxic–Ischemic Encephalopathy

Abstract: The consequences of therapeutic hypothermia for neonatal hypoxic-ischemic encephalopathy are poorly understood. Adverse effects from suboptimal rewarming could diminish neuroprotection from hypothermia. Therefore, we tested whether rewarming is associated with apoptosis. Piglets underwent hypoxia-asphyxia followed by normothermic or hypothermic recovery at 2 hours. Hypothermic groups were divided into those with no rewarming, rewarming at 0.5 °C/hour, or rewarming at 4 °C/hour. Neurodegeneration at 29 hours wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 46 publications
2
100
0
Order By: Relevance
“…Research on hyperthermia is lagging and further study of the underlying molecular mechanism is needed. It is known that apoptosis contributes to hyperthermia-induced tumor killing alone or when combined with other therapies [36]. Initiation of apoptosis directly regulates cell fate decisions and the ratio of Bcl-2 family members is a crucial modulating factor in the process [37].…”
Section: Resultsmentioning
confidence: 99%
“…Research on hyperthermia is lagging and further study of the underlying molecular mechanism is needed. It is known that apoptosis contributes to hyperthermia-induced tumor killing alone or when combined with other therapies [36]. Initiation of apoptosis directly regulates cell fate decisions and the ratio of Bcl-2 family members is a crucial modulating factor in the process [37].…”
Section: Resultsmentioning
confidence: 99%
“…Following 72 hours of cooling, infants should be slowly rewarmed (0.5°/hour). This is based on animal data showing increased seizures68 and increased cortical apoptosis69 with rapid rewarming. Longer or deeper cooling to <33.5° and/or for >72 hours has not been shown to be of benefit, and is harmful 70…”
Section: Neuroprotective Therapy In Hiementioning
confidence: 99%
“…[1] However, approximately half of survivors have persistent neurodevelopmental disabilities despite receiving hypothermia. [1, 2] We theorize that adverse effects from delaying the induction of hypothermia [3] and rewarming [4, 5] may be partially responsible for these neurologic impairments. We previously demonstrated that rewarming increases cortical neuronal apoptosis and caspase-3 cleavage after hypoxia-ischemia (HI) in a piglet model.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that rewarming increases cortical neuronal apoptosis and caspase-3 cleavage after hypoxia-ischemia (HI) in a piglet model. [4] Hypothermia and rewarming also promote glial apoptosis in the white matter, an effect that may be independent of HI in some brain regions. [5] Cortical and white matter injuries on MRI predict neurodevelopmental and motor impairments in survivors of HIE.…”
Section: Introductionmentioning
confidence: 99%